Effect Of Sensory Plate-Guided Exercises on Pain Reduction and Functional Outcomes After Total Knee Replacement - Bohra, Mustafa; Khan, Jafar; Pal, Renuka; Shandilya, Anurodh; Sharma, Subash; Arora, Shubham; Pinjara, Farukh Mohammad; Chauhan, Tina; Sharma, Deepak; Ramawat, Prashant (Journal of Neonatal Surgery, 2025)
Background: Total Knee Replacement (TKR) is a common surgical intervention for advanced knee osteoarthritis, yet post-operative pain and functional limitations often persist. Sensory plate-guided rehabilitation exercises may enhance postural stability, foot biomechanics, and pain reduction during recovery [1]. Objective: To evaluate the effect of sensory plate-guided exercises on pain reduction and functional outcomes in patients following TKR. Methods: An experimental study was conducted with 30 patients (male: 16, female: 14) aged 40–70 years who underwent TKR. Participants were recruited from the Department of Physiotherapy, Pacific Medical College and Hospital, Udaipur. Patients performed a six-week supervised rehabilitation program, including ankle-toe movements, quadriceps and hamstring isometrics, VMO activation, gluteal and hamstring strengthening, calf raises, and static cycling on sensory plates, five times per week. Outcome measures included the Numerical Pain Rating Scale (NPRS) for subjective pain and baropodometric parameters (load distribution, mean pressure, peak pressure, foot and body barycenter, C.O.P. distance) for functional assessment. Pre- and post-intervention scores were analyzed using paired t-tests, with significance set at p < 0.05 [2,3]. Results: Post-intervention, NPRS scores significantly decreased from 7.8 ± 0.83 to 3.7 ± 0.9 (p < 0.001), indicating substantial pain reduction. Baropodometric analysis demonstrated significant improvements in load distribution (72.23 ± 3.65% to 70.26 ± 3.50%, p = 0.032), mean pressure (34.45 ± 1.06 kPa to 33.21 ± 1.16 kPa, p = 0.045), foot barycenter (21.35 ± 2.03 mm² to 19.54 ± 2.09 mm², p = 0.027), body barycenter (91.48 ± 1.02 mm² to 59.83 ± 1.07 mm², p = 0.003), and C.O.P. distance (139.5 ± 4.98 mm to 106.7 ± 5.20 mm, p = 0.018). Peak pressure during contact and propulsion phases showed non-significant changes, suggesting targeted interventions may be required for phase-specific gait improvement [4,5]. Conclusion: Sensory plate-guided exercises significantly reduced pain and enhanced postural stability and foot function in post-TKR patients. Incorporating sensory plate-based rehabilitation may optimize functional recovery and improve gait mechanics after knee replacement surgery [6].